The intragranular textures of aggregates and its correlation to the physical properties - Azimah Hussin; Colin Poole (Universiti Kebangsaan Malaysia, 2010)
To evaluate the correlation of the intragranular textures on the physical properties of coarse aggregates, four aggregates samples consisting of three granitoid sources and one limestone have been studied. The role played by intragranular textures (mineral assembladge, grain size and grain boundaries) in influencing the physical properties are potentially significant to the fact that such textural variation may complicate the aggregate strength. This study indicates that the aggregates exhibited variation in textural habits. The granitoid aggregates, which is rich with silicate composition has typical heterogranular textures of porphyritic and equigranular grain structures. Whereas the limestone aggregate comprises of bioclast and peloid allochems cemented by micrite and spar. The granitoid aggregates showed better dispersed characters and had extremely interlocking crystal boundaries which have more physical strength compared to a carbonate aggregate.